Effect of intrinsic magnetic field decrease on the low-to-middle latitude ionosphere-thermosphere dynamics simulated by GAIA - Tao, Chihiro; Jin, Hidekatsu; Shinagawa, Hiroyuki; Fujiwara, Hitoshi; Miyoshi, Yasunobu (2017)
18th EISCAT symposium Session E7: Space weather and modelling May 27 (Sat), Poster Session conference object